Plant pets : 27 cool houseplants to grow and love - Allen, Beatrice Boggs; Boggs, Belle (North Adams, MA : Storey Publishing, 2024)
In this book written specially for kids, Beatrice Boggs Allen tells all about the easiest, most fun, and affordable plants that can be grown indoors in pots. She shares her first-hand tips on caring for each plant, along with descriptions of each one's unique attributes, from air plants to succulents, terrariums, and even carnivorous plants!
Hello from Belle -- Hello from Bea -- Getting started -- Where to keep your plant pet -- Let's do a light test! -- What supplies do you need? -- Where to adopt -- Pet-safe plant pets -- Where a love of plants can take you -- Cool plant pets! -- Pothos: plant pets by the foot -- Mother of thousands: so many plant babies -- Venus flytrap: this plant eats what?? -- Air plants: no soil? no problem! -- Aloe vera: a medicine cabinet on your windowsill -- The indoor herb garden: eat your pets -- Moss: your softest, fuzziest plant pet -- Moth orchid: your showiest pet -- Keeping your plants (and love of plants) alive -- Plant pet care and feeding -- Play with your pets (and learn from them, too) -- Plant matchmaker.
3-6
Keywords: Indoor gardening -- Juvenile literature; House plants -- Juvenile literature; Indoor gardening; House plants; Informational works